New species and new records of mites of the genus Stigmaeus (Acari: Prostigmata: Stigmaeidae) from Crimea - Khaustov, Alexander A. (Zootaxa, 2014)
Three new species of the genus Stigmaeus Koch, 1836 (Acari: Stigmaeidae) are described from various habitats in Crimea: Stigmaeus kuznetsovi sp. nov. from nests of Microtus socialis (Rodentia: Cricetidae); S. mitrofanovi sp. nov. from galleries of Pityogenes bistridentatus (Coleoptera: Curculionidae) under the bark of Pinus pallasiana, and S. silvestris sp. nov. from rotten log of Pinus pallasiana. Stigmaeus corticeus Kuznetsov and Wainstein, 1977 and S. maraghehiensis Bagheri and Ueckermann, 2012 are recorded for the first time in Crimea. A key to species of the genus Stigmaeus of Crimea is provided.